The connections and disconnections between teacher education policy and research: reframing evidence. (2nd January 2021) - Mayer, Diane
ABSTRACT: This paper examines the connections and disconnections between teacher education policy and research, and considers future opportunities for teacher education research by rethinking the notion of evidence as it is conceptualised in current policy debates. Historically, teacher education was positioned as a training issue, then as a learning issue, and more recently it has been framed as a policy problem requiring significant reform. By analysing the influences on current teacher education policy, this paper argues that we are now in a second stage of the 'teacher education as a policy problem' phase. Teacher education is now a politically constructed and ideological policy problem and the associated discourses of evidence are contributing to disconnections between teacher education research and policy. Drawing on findings from a large-scale longitudinal study investigating the effectiveness of teacher education that highlighted the complex and non-linear processes of learning teaching and doing teaching, I argue that singular thinking about the purpose of teacher education as only preparing teachers must be problematised. I suggest that calls for evidence, that are so prevalent in current policy, must be interrogated and reframed if compelling and convincing connections between teacher education policy and research are to be realised.